Effects of Polymerization Mode and Interaction with Hydroxyapatite on the Rate of pH Neutralization, Mechanical Properties, and Depth of Cure in Self-Adhesive Cements - Camargo, Fabiana S. A. S.; González, Alejandra H. M.; Alonso, Roberta C. B.; Di Hipólito, Vinicius; D'Alpino, Paulo H. P. (European Journal of Dentistry, 2019)
Objective The aim of the study was to evaluate the physicochemical properties of self-adhesive resin cements associated with hydroxyapatite (HAp) according to the polymerization activation.Materials and Methods Specimens of cements (PermaCem 2.0 [DMG]; MaxCem Elite [Kerr], and RelyX U200 [3M ESPE]) were distributed into three groups: activation mode; self-cured and dual-cured modes; and association or not with HAp powder mode. The pH neutralization was evaluated as a function of time. Flexural strength and elastic modulus were also tested (0.5 mm/min.). The depth of cure was also analyzed using the scraping test (ISO 4049). Infrared spectroscopy was also used to collect the spectra of specimens to evaluate the chemical bonds. Statistical comparisons were conducted at 5% of significance.Results The aggressiveness of the self-adhesive resin cements evaluated varied among the materials with a tendency for neutralization. Self-cure groups exhibited lower pH throughout the entire evaluation when compared with that of the dual-cure ones, irrespective of the addition of HAp. MaxCem Elite when photoactivated was the only cement influenced by the addition of the HAp in terms of mechanical properties. The self-adhesive cements tested presented equivalent depth of cure based on the ISO 4049 requirements, regardless of the evaluated factors.Conclusions Based on the parameters evaluated, the results demonstrated that most of the self-adhesive cements remained unaltered or improved when mixed with HAp, regardless of the activation mode.
Keywords: activation mode; hydroxyapatite; mechanical properties; self-adhesive resin cements